Influence of priming and nitrogen on growth behavior of buckwheat (Fagopyrum esculentum) in rainfed condition of midhill in Nepal - Gairhe, J. J.; Bhusal, T. N.; Neupane, H. (Journal of the Institute of Agriculture and Animal Science, 2018)
An experiment was conducted during winter, 2010/11 at IAAS, Lamjung with the objective of studying effect of seed priming and nitrogen levels on yield and yield attributing characters of buckwheat. Altogether, there were 9 treatments of seed priming hours (0, 18 and 36) combined with nitrogen levels (30, 45 and 60 kg/ha). The experiment was laid out in randomized complete block design and each treatment was replicated thrice. The seed priming of 36 hours had resulted in significantly higher germination percentage in both 15 days after sowing (DAS) (4.40%) and 30 (DAS) (5.74%) The total germination percentage was also significantly higher (48.4%) with 36 hr seed priming. The main and interaction effects of seed priming and nitrogen levels had significant influence on days to 50% flowering. The dry biomass per plant, grain yield, straw yield, harvest index and percentage moisture content of biomass at harvest were found non-significantly different due to seed priming and nitrogen levels. The highest value for dry matter accumulation per plant (5.24 gm/plant), straw yield (8706 kg/ha) and % moisture content (71.0%) was recorded with 36 hr seed priming whereas the highest value for grain yield (1599 kg/ha), and harvest index (19.8) was obtained with 18 hr seed priming. Likewise, dry matter accumulation (5.38 gm/plant), grain yield (1575 kg/ha) and harvest index (22.0) was found highest in 45 kg N/ha. Similarly, the straw yield (9153 kg/ha) and % moisture content (75.3%) was found highest in the treatment with 60 kg N/ha. The interaction effect between nitrogen level and priming was found non-significant and the highest grain yield (2091 kg/ha) was obtained from 18 hr seed priming with 45 kg N/ha. Phosphorus consumption rate was intrestingly higher in buckwheat plot with nitrogen application. Moderate consumption of potassium was also observed while nitrogen content in soil remain apparantly unchanged and similar was the case with soil pH and organic matter content. Application of phosphatic fertilizer would be benefitial for buckwheat cultivation. Further experiment should be done to verify the effective dose of fertilizer. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, Page: 47-54